Case Study: Nursing Care For Anxiety In Psychosomatic Patients With Complaints Of Palpitations And Chest Pain Using A Hypnotherapy Approach - Iwan Samsugito; Dwi, Nopriyanto; Siti, Riyani (Fakultas Kedokteran, Universitas Mulawarman, 2024)
Background: Anxiety is an unclear fear accompanied by feelings of uncertainty, helplessness, isolation, and insecurity, which are characterized by physical, mental, and behavioral disorders such as chest pain, palpitations, increased blood pressure, shortness of breath, heartburn, muscle aches, restlessness, confusion, decreased level of concentration, avoidance of particular objects or situations, sleep disturbances. Anxiety can cause psychosomatic disorders. Objective: This study is to provide an overview of anxiety nursing care for psychosomatic patients with complaints of palpitations and chest pain using hypnotherapy. Method: research using a case study approach. The analysis was carried out in four meetings, from assessment to evaluation. The anxiety measuring tool uses the Zung Anxiety Self Rating Scale questionnaire. Nursing actions are carried out using relaxation techniques, direct suggestions, verbalization, and desensitization. Results: Hypnosis can reduce the patient's anxiety level and experience improvements in signs and symptoms in the form of being able to teach calmly and focused, being able to pray in congregation comfortably, being able to participate in taklim assembly events with friends, being able to ride a motorbike calmly and when there is a traffic light there is no feeling of worry anymore. , sleep is comfortable, blood pressure 120/80 mmHg, pulse 80 x/minute, can understand that the heart condition is good and this is a problem of the mind and there is no chest pain. Conclusion: Anxiety patients who experience psychosomatic complaints of heart palpitations and chest pain can be treated with hypnosis using direct suggestion, verbalization, and desensitization methods.